EFFECT OF A THERMOGENIC SUPPLEMENTATION ON POST AEROBIC EXERCISE HEMODYNAMIC RESPONSES IN HEALTHY YOUNG MEN - e Silva, Vilton Emanoel Lopes de Moura; Silvino, Valmir Oliveira; Rodrigues Júnior, Jefferson Fernando Coelho; Sena, Alyson Felipe da Costa; Amorim, Carlos Eduardo Neves; Cabido, Christian Emmanuel Torres; dos Santos, Marcos Antônio Pereira (Revista Contexto & Saúde, 2020)
Introduction: The use of food supplements with esthetic or performance-enhancing goals has been largely investigated. Thermogenics are supplements that increase energy expenditure through thermogenesis and are widely consumed by individuals seeking to improve body composition and exercise performance. Objective: To evaluate the effects of a commercially available thermogenic supplement on post-exercise blood pressure responses. Materials and Methods: Twenty-seven healthy thermogenic supplements users participated in the study. Nine were assigned in the control group (21.67 ± 1.87 years), nine in the thermogenic group (24.00 ± 4.18), and nine in the placebo group (23.67 ± 3.04). The volunteers performed a treadmill aerobic exercise session for 60 minutes at 65 to 85% max heart rate. The hemodynamic variables were measured at rest and during 60 minutes in the post-exercise recovery. The normality of the data was evaluated using the Shapiro-Wilk test. Baseline momentum and post-exercise recovery were analyzed using the two-way ANOVA test (group versus time factors), with Bonferroni post-hoc test. The level of statistical significance was set at p <0.05. Results: The thermogenic supplement did not significantly compromise post-exercise hypotension when compared to the other groups. However, thermogenic supplementation increased the blood pressure in >5 mmHg, which reportedly plays an important role in cardiovascular diseases. Conclusion: The use of the thermogenic Lipo 6 Black Ultra Concentre Nutrex ® did not alter PEH in healthy youngsters. However, since an increase in the blood pressure was observed, this supplementation must be administered with caution.